The reality of succession planning Under the retirement law No. (26) of 2019 / Applied research in the medical city - Ali, Atheer Tahseen; D. Al –Zubaid, Ghani i (Journal of Economics and Administrative Sciences, 2021)
This research aims to know the reality of succession planning in the researched organization and how it occupies the important jobs in the organization and its readiness for sudden and urgent events that lead to the vacancy of these jobs, and the importance of this research is that it is one of the rare Arab and Iraqi studies and research in this field, as it is one of the first researches It deals with the reality of succession planning in light of the retirement law No. (26) of 2019, and the research problem was the absence of consecutive planning programs and the weak preparation of suitable candidates to face sudden and urgent conditions as replacements for current leaders who occupy the leading and key positions in the department The Medical City, as the research sample included all the directors of the departments in the General Administration / Medical City Department, who numbered (8) eight department directors, and who nominated (29) twenty-nine candidates for the succession planning program to fill the positions of the departments administration in the event of their vacancy in the future, and The researcher has adopted the case study approach for the possibility of collecting more than one research method at one time, and data was collected using a personal and job information form and a performance evaluation form, in addition to questions of personal interviews and observation during field coexistence as well as official documents obtained during local visits It is used for the organization, and the data has been analyzed through the Excel program, and some statistical methods such as (the arithmetic mean and the percentage) have been used to analyze the data of the candidates, and the most prominent results that the researcher reached is the absence of succession planning programs that explain how to occupy the leading, key and critical positions In anticipation of any emergency event in the research organization, as well as the presence of candidates who have high performance ratings between (good and excellent) that qualify them for future management positions as successors to current managers